(untitled) (REMUNOM, 2025)
Breast cancer is the most common malignant neoplasm among women in Brazil and one of the main causes of mortality, constituting a public health problem of great impact. The high incidence of the disease, combined with regional inequalities in access to prevention, diagnosis and treatment, highlights the need to understand its epidemiological aspects. In view of this scenario, the present study aimed to analyze breast cancer cases in Brazil, between the years 2020 and 2024, based on data made available by DATASUS, seeking to identify patterns of occurrence by regions and age groups, as well as trends in the period analyzed. This is a descriptive study, with a quantitative and cross-sectional approach, based on secondary data from mammograms performed within the scope of the Unified Health System (SUS). The variables were organized by age groups and geographic regions, and were submitted to statistical and graphical analysis for a better understanding of the distribution of cases. The results showed continuous growth in registrations, from 1,868,352 in 2020 to 3,609,277 in 2024, with the highest concentration in the Southeast Region, followed by the Northeast. Most cases occurred in women over 50 years of age, although a gradual increase was observed among younger women. The North and Central-West regions had lower rates, which may reflect underreporting and difficulties in accessing health services. It is concluded that, despite the expansion of screening programs, regional and age inequalities still persist, reinforcing the importance of public policies that expand access to preventive exams, awareness campaigns and early detection strategies. Such measures are essential to reduce mortality and improve the quality of life of women affected by the disease